High-frequency frontal displacements south of san jorge gulf during a tidal cycle near spring and neap phases biological implications between tidal states - Carbajal, Juan Cruz (2018)
San Jorge Gulf (SJG) is a region of high biological productivity that supports important shrimp (Pleoticus muelleri) and hake (Merluccius hubbsi) fisheries, as well as high marine biodiversity associated, in part, with a tidal front located in the southern part of the gulf. In situ high-resolution cross-frontal measurements were collected using a remotely operated towed vehicle to characterize the three-dimensional structure of the tidal front and to investigate how its position varies during the semidiurnal tidal cycle (high/low) and the spring to neap transition, together with its impact on the distribution of nutrients and chlorophyll-a. Estimates of tidal height and flow velocity derived from a numerical model support the conclusion that frontal displacements mostly result from advec-tion by cross-frontal tidal currents. The frontal position was also modified by baroclinic instabilities that significantly distort the front. Measurements reveal intrusions of low-salinity, nutrient-rich waters from the mixed side into the pycnocline on the stratified side cause a subsurface chlorophyll-a peak near the neap phase. Most prior studies of fronts in the SJG have been limited to their surface manifestations because they were conducted using satellite images. This article aims to contribute to the understanding of the complex southern tidal front dynamics, highlighting that maximum primary productivity occurs in a subsurface layer that is not visible by satellite sensors.